Adopsi Pekerjaan Konveksi Rumahan sebagai Transformasi Mata Pencaharian di Desa Lebakmuncang, Bandung - Muhammad Mikail Yusuf Kamal; Hanifa Najma Kamila; Michelle Phoebe Yulia; Nur Mala Santi; Sheren Aurelia Sulaiman (Saskara : Indonesian Journal of Society Studies, 2026)
Technological development has brought significant changes to the socio-economic life of communities, particularly in the area of Lebakmuncang Village, Bandung. One sector that has driven the transformation of employment in Lebakmuncang Village is home convection, which has become increasingly popular alongside traditional occupations such as farming. The purpose of this study is to examine how home convection in Lebakmuncang Village has been adopted and how it has become a form of livelihood transformation for the local community. This research employs a qualitative approach with purposive sampling as the data collection method. The study was conducted from November 28 to 30, 2025, and involved six informants: two home convection owners from ATO Official and APIH Collection, three workers' home convection, and one village figure. The results show that the transformation process did not immediately change the socio-economic conditions of the people of Lebakmuncang Village but occurred gradually. Home convection has become one of the preferred occupations among villagers because the workplaces are generally located close to their homes and operate continuously.